Impact of reorganized interfacility transfer on emergency obstetric care in Nara prefecture, Japan. (2019) - KOBAYASHI, HIROSHI; AKASAKI, MASAYOSHI; TSUNEMI, TAIHEI; AKASAKA, JURIA; NARUSE, KATSUHIKO; SADO, TOSHIYUKI
No abstract available